Crosses with Amut Bmut homokaryons of Coprinus cinereus - Y Liu; J D Granado; E Polak; U Kües (Fungal Genetics Reports, 1999)
In this paper we describe the initial genetic analysis of some developmental REMI and UV mutants of the self-compatible homokaryon Amut Bmut. We show that such homokaryons can mate with each other although in fruitbodies we often found spores of only one parent. Crosses with monokaryons of different mating types gave some indications about numbers of mutations and linkage of genetic markers. In most cases, however, we observed an uneven distribution of markers, most likely because of loss of certain progeny. Our results necessitate the construction of monokaryons as closely related to homokaryon AmutBmut as possible but with different mating type loci.